(untitled) (Philological Studies, 2019)
The grain, flour and bread had a particularly important role in the customs of the ancient Macedonians. Regarding the tradition for the founding of the Macedonian Kingdom, the magic ("double") rising of the bread of Perdiccas, the first Macedonian king of the Argead dynasty, is stated. The sources noted an example for using the flour for announcement of the boundaries of a new city in its establishment. Namely, in this way was marked the foundation of the famous Alexandria in Egypt, where the ground plan of the city that had a shape of chlamys, was drawn with flour from barley. Concerning the wedding of Alexander III of Macedon with Roxana, a Macedonian wedding custom of cutting the bread with a sword is described, too. This paper deals with the analysis of these fragments, which although sparse, confirm the sacred symbolism of grain, bread and flour among the ancient Macedonians. Traces of this symbolism can be found today in the modern tradition, which among other things allow us to penetrate deeper into the essence of these customs.